Continuity and nationality of the Republic of Lithuania - Žalimas, Dainius (Politologija, 1997)
This article was written under the influence of the Seminar "Citizenship and State Succession," which was held in Vilnius on 16-17 May, 1997, at the initiative of the Council of Europe. The seminar was dealing with the issues of nationality in new European states which appeared after the dissolution of the USSR and Yugoslavia. The practice of three Baltic States was also briefly discussed. However, the author postulates that the case of Baltics is a specific one. Lithuania, Latvia, and Estonia cannot be regarded as new States because they have restored their independence in 1990-1991 on the basis of de jure continuity of their statehood. These States were illegally occupied and annexed by the USSR in 1940. Thus, according to the principle of ex injuria non oritur jus, their statehood and nationality prevailed, i.e., the nationality of the three Baltic States was recognized to those persons who possessed one of these nationalities in the interwar period and to their descendants. Only after that were the issues of nationality of other inhabitants of the Baltic States solved. This solution is not connected to the issues of State succession, as these States are not successors of the USSR. The author examines the practice of one of the Baltic States, the Republic of Lithuania, concerning the issues of nationality in his aim to show the specificity of the Baltic States in comparison with the former republics of the USSR and Yugoslavia.
Keywords: -